PENGENYAMPINGAN PIDANA DENDA BAGI PENJUAL KHAMAR: QANUN, PUTUSAN HAKIM DAN TEORI HUKUM PROGRESIF - Ihdi Karim Makinara (Universitas Islam Negeri Ar-Raniry, 2017)
This study discusses criminal prosecution of fines for perpetrators of jarimahkhamar crimes in Aceh. Uqubatta'zir was previously formulated alternative cumulative in Article 26 paragraph (2) Qanun NAD Number 12 Year 2003 and has been used in Decision Number 22/JN/2009/MS.Mbo.The judges of the MahkamahSyari'iyyahMeulaboh did not impose a fine on the convicted person.The culprit is a non-Muslim, he has a family, and this is his second crime. While Article 16 paragraph (1) and (2) Qanun Aceh Number 6 of 2014 formulates a fine with an alternative formulation. If the formulation in these two paragraphs finds a concrete legal event, what judge will use a fine to the same perpetrator. Judge is not a funnel of law, so it must give justice according to the situation of the convicted person. Because the criminal not only reply, but educate and prevent.